2018
DOI: 10.1016/j.jana.2018.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Anal Dysplasia Screening into the Primary Care of Persons Living with HIV

Abstract: Anal dysplasia can lead to anal cancer, which affects persons living with HIV (PLWH) more than people in the general population. Screening for anal dysplasia is recommended to detect anal cancer at an early stage. The aim of our process improvement project was to improve compliance and consistency in implementing anal dysplasia screening for PLWH receiving care at a Ryan White facility covering 18 counties in western North Carolina. There were 291 PLWH screened for anal dysplasia during the 9-month data-gather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 7 publications
1
4
0
1
Order By: Relevance
“…Consistent with previous research [ 40 42 ], the interviewee acknowledged the feasibility of nesting cancer control program associated with HPV infection into healthcare in general, and HIV care in particular. Almost all categories of participants thought that setting up another disease specific or verticalized program is neither desirable nor possible.…”
Section: Discussionsupporting
confidence: 65%
“…Consistent with previous research [ 40 42 ], the interviewee acknowledged the feasibility of nesting cancer control program associated with HPV infection into healthcare in general, and HIV care in particular. Almost all categories of participants thought that setting up another disease specific or verticalized program is neither desirable nor possible.…”
Section: Discussionsupporting
confidence: 65%
“…Likewise, different from Newman et al's study, whose study population described the anus as "hidden" or "private," this male population discussed with female friends what routine health care for receptive partners should entail. 27 The differences between our study population about using language such as "anal pap" and "anal pap smear" as well as emphasizing identity as a "bottom" and receptive anal sex as opportunities to improve public health messaging concerning HRA require examination of the uniqueness of our population. The participants of our study were directly recruited from Anoscopy clinic, and our population demonstrated high levels of adherence to HRA.…”
Section: Discussionmentioning
confidence: 97%
“…Likewise, different from Newman et al’s study, whose study population described the anus as “hidden” or “private,” this male population discussed with female friends what routine health care for receptive partners should entail. 27 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Por consiguiente, el hecho de que aproximadamente 1 de cada 4 pacientes evaluados en nuestro estudio presentara condilomas perianales nos invita a implementar tamización de rutina (36,37); incluso, si el paciente refiere conductas sexuales seguras, dado que no es posible establecer que se trate de un contagio reciente, ya que el VIH altera el aclaramiento de la infección por VPH (38)(39)(40).…”
Section: Discussionunclassified